2001
DOI: 10.1007/s002160101032
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium and ruthenium dioxide-modified graphite–ethylene/propylene/diene and graphite–Teflon composite electrodes as amperometric flow detectors. Application to the determination of methionine

Abstract: The flow injection amperometric performance of solid composite graphite electrodes with ethylene/propylene/diene (EPD) or Teflon as binding agents, and with Ru or RuO2 particles as electrocatalytic modifiers has been compared. Both, Ru and RuO2 modified electrodes exhibited electrocatalytic properties on the methionine oxidation process in alkaline media. The electrodes composition and the hydrodynamic and chemical variables were optimized. Graphite-EPD (GEPD) electrodes showed a better analytical performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The performance of different electrodes used for the amperometric oxidation of methionine was evaluated. Graphite electrodes modified with ethylene/propylene/diene (EPD) or Teflon powder as binding agents, containing Ru or RuO 2 particles as electrocatalytic modifiers, were compared 171. RuO 2 ‐graphite‐EPD electrodes showed a better sensitivity, reproducibility, and mechanical and chemical stability in comparison with graphite‐Teflon electrodes.…”
Section: Representative Studies Involving Amperometric Detection and mentioning
confidence: 99%
“…The performance of different electrodes used for the amperometric oxidation of methionine was evaluated. Graphite electrodes modified with ethylene/propylene/diene (EPD) or Teflon powder as binding agents, containing Ru or RuO 2 particles as electrocatalytic modifiers, were compared 171. RuO 2 ‐graphite‐EPD electrodes showed a better sensitivity, reproducibility, and mechanical and chemical stability in comparison with graphite‐Teflon electrodes.…”
Section: Representative Studies Involving Amperometric Detection and mentioning
confidence: 99%
“…Noble metal nanoparticles, such as Au and Pt, have desirable electrochemical characteristics, such as excellent electrical conductivity, good electrocatalytic activity, and easy surface modification. It has been reported that the modification of metal nanoparticles onto the electrode surface reduces the overpotential of amino acid oxidation and can amplify the electrical signal differences of diastereomeric complexes [31,32]. Meanwhile, Pt nanoparticles (NPs) can be further surface-modified by PtÀ S interaction [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanical stability of mercury electrodes is low; they therefore require special handling and their use in flow analytical systems is limited. Other electrode materials that have been used in amperometric detection include glassy carbon (GC) [7,8], carbon paste (CP) [9,10] and gold [11,12]; recently, boron-doped diamond electrodes have become available [13,14]. These electrodes show good mechanical stability and allow surface or bulk modification, which increases their potential usefulness.…”
Section: Introductionmentioning
confidence: 99%